How do taxes react to changes in prices and economic activity? A case study for the State of Ceará - Dantas, Gabriel Costa Santos (2024)
This study investigates the impact of economic activity and inflation on the revenue of different segments of the Tax on operations related to the circulation of goods and on the provision of interstate, intermunicipal and communication transport services (ICMS). Given that the ICMS is the primary source of revenue for Brazilian states, understanding the factors that influence its collection becomes crucial for fiscal planning and budget management. To achieve these objectives, this study employs Bayesian Vector Autoregressions with Varying Constants (BTVCVAR) to investigate the dynamic relationship between these variables over twenty years, from 2003 to 2023. This study employed monthly data on various ICMS segments, inflation, and economic activity spanning from January 2003 to December 2023. The analysis results demonstrate that both local and national inflation exerted an influence on the revenue generated by the different ICMS segments over the examined period. Economic activity exhibited statistically significant effects solely on the retail sector. Furthermore, impulse response analysis revealed that the retail sector was the only one capable of positively influencing other sectors, namely wholesale trade, industry, and fuels. Understanding the dynamics between tax collection and other economic variables is crucial for policymakers to formulate the most effective strategies. A clearer understanding of how ICMS revenue behaves in response to changes in inflation and economic activity can support the state of Ceará in improving its planning of public revenues and expenditures.